Case Report: Novel IL10RB variant causing very early onset-inflammatory bowel disease - Usman, Yusuf; Ptak, Christopher P.; Cohran, Valeria C.; Nolan, Brian E.; Ahmed, Aisha; Khanolkar, Aaruni (Frontiers in Immunology, 2025)
BackgroundVery early onset-inflammatory bowel disease (VEO-IBD) can arise from monogenic defects affecting immune regulation. We report a male child with VEO-IBD caused by a homozygous, loss-of-function IL10RB variant (c.562T>G; p.C188G) that has not been previously reported for this disorder.Case PresentationA male infant of Hispanic descent was admitted to our hospital at the age of 8 months due to intractable colitis, perianal fistulas and growth faltering. Endoscopy at nine months of life revealed pancolitis and gastritis. Despite multiple courses of steroids and use of sulfasalazine, their disease remained active. Standard biologic therapies (infliximab and adalimumab) were trialed in the second year of life without improvement. Given the very early onset and severe phenotype, functional testing by phosflow to evaluate the IL-10 signaling pathway demonstrated the absence of STAT3 phosphorylation in response to IL-10 and follow up genetic testing identified a novel homozygous IL10RB missense variant (c.562T>G; p.C188G). Subsequent protein structure analysis using AlphaFold corroborated this loss-of-function phenotype. The patient’s condition was partially controlled with anakinra (IL-1 receptor antagonist) as a bridge therapy. At the age of 3 years, the patient underwent an allogeneic hematopoietic stem cell transplant (HSCT) from an unrelated umbilical cord blood donor; however, they experienced engraftment failure, likely due to persistent hyperinflammation and the choice of cord blood for HSCT. The patient continues to have active disease requiring on-going medical management and supportive care.ConclusionWe report a novel, loss-of-function IL10RB variant causing VEO-IBD, thus expanding the genotypic spectrum of this condition. This case highlights the diagnostic and therapeutic challenges of IL-10R deficiency–related VEO-IBD. It also underscores the importance of early recognition of monogenic causes of IBD, use of interim immunomodulatory therapies, and the need for optimal timing and donor selection for HSCT.